(untitled) (Research, Society and Development, 2021)
Globally, public expenditures related to mental health care have been the target of different economic evaluation studies, allowing for an understanding of the scenario that encompasses the effectiveness and cost of care. Objective: To analyze the cost of mental health care in the context of public funding. Methodology: Integrative review, without temporal delimitation. Used the PICO strategy for combinations of terms and use of the Boolean operator “AND”, covering databases: Medline via PubMed, LILACS, EMBASE, Web of Science, SCOPUS and COCHRANE LIBRARY. The level of evidence and methodological quality of each study were assessed. The PRISMA method was used. Results: 266 studies were found. After peer review, 16 selected to compose the review. Most (75%) of the surveys were carried out in European countries, from the perspective of service providers, mainly in the hospital and community context. The studies involved investigations related to indirect and direct costs, hospital doctors and non-medical hospitals: services, drug interventions, mental disorders, with emphasis on schizophrenia. They were measured using descriptive statistics, and analyzed using the microcosting method (43.7%), with a temporal variation from 1 to 36 months. As for the main findings, the impact on the use of services and pharmacological treatment stands out, as well as the description of some average monthly per capita values that were different in the economic evaluation carried out. Conclusion: This integrative review study provides information that can lead to management and clinical approaches that can improve and optimize aspects of public funding for mental health care.